Hemodynamics of transcatheter tricuspid valve replacement with Lux-Valve - Wei, Wang; Ning, Li; Xiaoping, Ning; Zhiyun, Xu; Bailing, Li; Chengliang, Cai; Fan, Yang; Guangwei, Zhou; Yifan, Bai; Lin, Han; Fan, Qiao; Fanglin, Lu (Frontiers in Cardiovascular Medicine, 2022)
Objective Transcatheter tricuspid valve intervention (TTVI) has emerged as an alternative treatment option for high-risk and inoperable patients with symptomatic tricuspid regurgitation (TR). However, scarce data in hemodynamic profiles were available on TTVI. In this paper, we attempt to report the hemodynamic profiles of LuX-Valve. Methods 30 patients from July 2020 to July 2021 were enrolled in this study. The patient was diagnosed with severe symptomatic TR. The clinical, invasive hemodynamic, and echocardiographic data were collected. Results The surgical success rate was 100%. The cardiac index and stroke volume increased sharply from 2.42(2.27, 2.85) and 47.8(43.6, 62.0) to 3.04 ± 0.63 and 57.2 ± 14.7, respectively. With the elimination of TR and the increase of forward blood flow of the tricuspid valve, the extravascular lung water [798.0 (673.0, 1147.0) vs. 850.3 ± 376.1, P < 0.01] increased subsequently. The peak right atrium pressure decreased after Lux-Valve implantation (21.0 ± 6.4 vs. 19.4 ± 6.5, P < 0.05). On the contrary, the nadir right atrium pressure increased [10.0(8.0, 15.0) vs. 12.0(10.0, 17.0), P < 0.01]. Notably, the right atrium pressure difference dropped sharply from 9.0(5.0, 13.0) to 5.0(4.0, 8.0) after Lux-Valve implantation. There was no significant change in the pulmonary artery pressure. The right atrium volume decreased from 128(83, 188) to 91(67, 167) mL at 1 month and 107(66,157) mL at 6 months. With the remolding of the right heart chamber, the tricuspid annulus diameter shrank significantly from 42.5 ± 5.6 to 36.6 ± 6.3 mm at 1 month and 36.0 (33.0, 38.0) at 6 months. Conclusion Invasive right atrium pressure may act as a potential candidate for TR evaluation and procedural guidance. Elimination of TR by LuX-Valve implantation improves the cardiac output and right atrium pressure and has no significant effect on the pulmonary artery pressure even with the increment of forward blood flow, suggesting the hemodynamic superiority of transcatheter tricuspid valve replacement but needs further study.